Catechol-O-methyltransferase Val158Met Genotype and Early-Life Family Adversity Interactively Affect Attention-Deficit Hyperactivity Symptoms Across Childhood - Abraham, Eyal; Scott, Marc A.; Blair, Clancy (Frontiers in Genetics, 2020)
Attention-deficit hyperactivity disorder (ADHD) is among the most commonly diagnosed psychiatric disorders of childhood. The dopaminergic system has been shown to have substantial effects on its etiology, with both functional Catechol-O-methyltransferase (COMT)Val158Met genotype and early-life environmental adversity involved in the risk of inattention and hyperactivity/impulsivity symptoms. In this prospective longitudinal study, we examined for the first time the impact of proximal and distal early-life family adversity and COMT Val158Met polymorphism gene - both the direct and the interactive effects, on children’s inattention and hyperactivity/impulsivity symptoms across childhood. Data came from the Family Life Project, a prospective longitudinal study of 1,292 children and families in high poverty from birth to 11 years. In infancy, data regarding socioeconomic (SES)-risk-factors, observed-parenting behaviors, and DNA genotyping were collected. In early and middle childhood teachers rated the occurrence and severity of the child’s ADHD symptoms. Multilevel growth curve models revealed independent effects of COMT, early-life SES-risk and negative parenting on inattention and hyperactivity/impulsivity symptoms in early and middle childhood. Significant gene-environment interactions were found, indicating that overall, carriers of at least one COMT158Met allele were more sensitive to early-life adversity, showing higher inattention and hyperactivity/impulsivity symptoms severity in childhood when exposed to high SES-risk factors in infancy, compared to Val-Val carriers. Findings provide new insights into the complex etiology of ADHD and underline the need for further investigation of the neuronal mechanisms underlying gene-environment interactions. Findings might have implications for prevention and intervention strategies with a focus on early-life family relationships in genetically at-risk children.